PT. PNM's Strategy in Preventing Misuse of Business Capital Loans in Bahoras Village, Gunung Tuleh District, West Pasaman - Tiara Amelia; Irwan; Sri Rahmadani (UNIB Press, 2025)
This study aims to describe the actors involved in the scope of business capital loans and to analyze PT's strategies. Permodalan Nasional Madani (PNM) in preventing such conservation in Nagari Bahoras, Gunung Tuleh District, West Pasaman Regency. The theoretical framework used is Anderson's (1979) public policy theory. This study employs a qualitative descriptive approach, using data collected through observation, in-depth interviews, and document analysis. This study involved 13 informants selected by purposive sampling. The findings indicate that actors who misused the loan funds included farmers, traders, and homemakers. The funds were diverted to non-productive uses, such as household expenses, debt repayment, children's education, and consumption—prevention strategies implemented by PT. PNM includes tightening loan SOPs, assessing business feasibility, increasing supervision, and imposing sanctions on clients who misuse loans. However, the implementation of these strategies remains suboptimal due to weak monitoring and inconsistent enforcement of sanctions.